Análise estrutural do depósito de au e cu da região de Paran, Peru - Pocay, Wagner Roberto Hansted [UNESP]; Simões, Luiz Sergio Amarante [UNESP] (My University, 2013)
Structural Analisys of the deposit of Au and Cu in Paran's region, Peru. This region located in the Huaura province, in central Peru, presents a deposit of gold and cupper, with low to medium sulphidation of epithermal character. The area was subject to geological-structural studies, was mapped in 1:5.000 scale. They are represented mainly by intermediate volcanics sequence from Cenozoic age of Calipuy Supergroup and a diorite related to the Coastal Batholit, of Cretaceous age. It was identified five litho-structural areas, four of that consist by lava flow, tuff an andesitic breccias of Calipuy Supergroup and one by the diorite. The area is located in a strong tectonized region into the ruptil regime, which have been identified three main fractures systems investigated in detail for kinematic characterization. The NW system, with steep dip to SW is the oldest and limits the main lito-structural domains. The NE system has dip around 60° to SE. The younger system has E-W direction, with dips around 80° to S. The three system are mineralized, the first and the second are the most important in volume and ore grade. The study of paleo-stress indicate which the first event is related to the compressive Andean tectonic, and the others two events reflect extensional processes.
Structural analysis of deposit and cu au region Paran, Peru
Keywords: Paleo-stress; Structural Analisys; Structural Characterization